To study the correlation between endometrial thickness on transvaginal sonography and endometrial histopathology in women with postmenopausal bleeding - Chaudhari, Leena; Satia, Meena N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Endometrial carcinoma is the most common malignancy of the female genital tract, ranking second to carcinoma cervix. It occurs primarily in postmenopausal women. Majority of women with endometrial cancer present with postmenopausal bleeding (90%) but in only about 15% of women is endometrial cancer the cause of postmenopausal bleeding. The objective of current study is to study the correlation between endometrial thickness on transvaginal sonography and endometrial histopathology in women with postmenopausal bleeding and whether endometrial thickness > 4mm is more suggestive of hyperplasia or carcinoma. Methods: The cases were selected from amongst the patients attending gynaecology OPD, who had history of postmenopausal bleeding or spotting per vaginum and were subjected to TVS followed by endometrial sampling by brush cytology Diagnostic Hysteroscopy was done which was followed by fractional curettage. The material obtained by sampling studied for endometrial histopathology. Results: Atrophic endometrium’s followed by proliferative endometrium was the most common histological findings and 9% patients had adenocarcinoma. Mean endometrial thickness on TVS was 5.97mm for atrophic histology and 11.95 mm for carcinoma. Conclusions: Postmenopausal bleeding, should always be taken seriously, no matter how minimal or nonpersistent it is, because though majority of causes underlying postmenopausal bleeding are benign, endometrial carcinoma may be seen in around 10% cases. So, patients with PMB must undergo thorough evaluation by endometrial sampling which cannot be replaced by transvaginal sonography which though has more sensitivity to detect endometrial thickening, at the same time, has low specificity for detection of malignancy.